Impact of hypoglycemic drugs on the course of COVID-19 in patients with type 2 diabetes mellitus - Yasmin Ahmed Ali El-Taravi; Emiliya S. Rassadina; Valeriya S. Kuzenkova; Tatiana S. Kokorina; Alina I. Dzarasova; Ella T. Rogava; Irina A. Kuzina; Narine S. Martirosyan; Nina A. Petunina (LLC "MEDIAFORMAT", 2023)
Diabetes mellitus and hyperglycemia are independent risk factors for morbidity, severe course, and adverse outcomes of a nevel coronavirus infection. The article discusses the features of the course of COVID-19 in patients with diabetes. Chronic hyperglycemia is associated with endothelial dysfunction, increased expression of pro-inflammatory cytokines, and a hypercoagulable state that aggravates the course of a viral infection. In turn, COVID-19 is associated with an increased risk of manifestation of diabetes mellitus, the SARS-CoV-2 virus can act as a potential trigger agent. There are still a number of unresolved questions, in particular, whether the virus can cause the manifestation of a special type of diabetes. No less relevant is the issue of optimal hypoglycemic therapy in patients with type 2 diabetes and COVID-19. Hypoglycemic therapy, by influencing various links in the pathogenesis of diabetes mellitus and lowering the level of glycemia, can potentially reduce the risks of complications and severe course of COVID-19 in patients with diabetes mellitus.